The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1534/genetics.114.170589
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Development in Caenorhabditis elegans Is Regulated by Inhibition of an MLK MAP Kinase Pathway

Abstract: We show that loss-of-function mutations in kinases of the MLK-1 pathway (mlk-1, mek-1, and kgb-1/jnk) function cellautonomously in neurons to suppress defects in synapse formation and axon termination caused by rpm-1 loss of function. Our genetic analysis also suggests that the phosphatase PPM-1, like RPM-1, is a potential inhibitor of kinases in the MLK-1 pathway. IN Caenorhabditis elegans, the ubiquitin ligase Regulator of Presynaptic Morphology 1 (RPM-1) regulates neuronal development by inhibiting the DLK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
(43 reference statements)
0
17
1
Order By: Relevance
“…Several downstream proteins that mediate the function of RPM-1 in neuronal development have been identified ( Baker et al 2014 , 2015 ; Grill et al 2007 , 2012 ; Liao et al 2004 ; Nakata et al 2005 ; Tulgren et al 2014 ; Yan et al 2009 ). For example, RPM-1 positively activates GLO-4 to regulate the GLO-1 Rab GTPase ( Figure 6A ) ( Grill et al 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several downstream proteins that mediate the function of RPM-1 in neuronal development have been identified ( Baker et al 2014 , 2015 ; Grill et al 2007 , 2012 ; Liao et al 2004 ; Nakata et al 2005 ; Tulgren et al 2014 ; Yan et al 2009 ). For example, RPM-1 positively activates GLO-4 to regulate the GLO-1 Rab GTPase ( Figure 6A ) ( Grill et al 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…After more than a decade of research, the PHR proteins have emerged as key, conserved regulators of neuronal development and axon degeneration ( Conforti et al 2014 ; Po et al 2010 ). Numerous downstream effector proteins and pathways that mediate PHR protein function have also been discovered ( Baker et al 2014 , 2015 ; Collins et al 2006 ; Grill et al 2007 , 2012 ; Liao et al 2004 ; Murthy et al 2004 ; Nakata et al 2005 ; Tian et al 2011 ; Tulgren et al 2014 ; Xiong et al 2012 ; Yan et al 2009 ). Despite this important progress, a lingering question has remained: how does the function of PHR proteins during development impact behavior?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…elegans regulator of presynaptic morphology 1 (RPM-1) is an intracellular signaling hub that regulates axon termination, and is orthologous to Drosophila Highwire, mouse Phr1 and human Pam/ MYCBP2 (Borgen et al, 2017;Feoktistov and Herman, 2016;Grill et al, 2016;Opperman and Grill, 2014;Schaefer et al, 2000). RPM-1 acts as a ubiquitin ligase to inhibit MAP3K proteins, such as DLK-1 and MLK-1 (Baker et al, 2015;Collins et al, 2006;Nakata et al, 2005). Notably, RPM-1 also uses signaling mechanisms that are independent of its ubiquitin ligase activity (Baker et al, 2014;Grill et al, 2007;Grill et al, 2012;Tulgren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies in Drosophila showed that Highwire inhibition of Wallenda/Dlk impacted the JNK ortholog, Basket, and the transcription factor c-Fos [ 48 ]. While these initial studies suggested that different MAP kinase pathways might be regulated by RPM-1 and Highwire, this was not the case as subsequent genetic analysis indicated that RPM-1 regulates a second MAPK pathway composed of the MAP3K MLK-1, the MAP2K MEK-1 (MKK7 ortholog) and the JNK isoform KGB-1 [ 46 , 55 , 56 ] (Fig. 1a ).…”
Section: Introductionmentioning
confidence: 99%